Eulogy for the Lord Cooke of Thorndon - Elias, Sian (Victoria University of Wellington Law Review, 2008)
This eulogy was given at the funeral of Lord Cooke of Thorndon at St Paul's Cathedral, Wellington on 4 September 2006.